2010
DOI: 10.1371/journal.pone.0010167
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adherence and Expression of Virulence Genes in a Lineage of Escherichia coli O157:H7 Commonly Associated with Human Infections

Abstract: BackgroundEnterohemorrhagic Escherichia coli (EHEC) O157:H7, a food and waterborne pathogen, can be classified into nine phylogenetically distinct lineages, as determined by single nucleotide polymorphism genotyping. One lineage (clade 8) was found to be associated with hemolytic uremic syndrome (HUS), which can lead to kidney failure and death in some cases, particularly young children. Another lineage (clade 2) differs considerably in gene content and is phylogenetically distinct from clade 8, but caused sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 62 publications
(108 reference statements)
4
59
0
Order By: Relevance
“…39 Moreover, the clade that is associated with more severe symptoms also had a higher ability to attach to epithelial cells and had higher virulence gene expression. 40 This suggests that bacteriophage repertoires are relatively stably associated with individual lineages within EHEC O55:O157.…”
Section: The Influence Of the Accessory Genome On Bacterial Pathogen mentioning
confidence: 99%
See 1 more Smart Citation
“…39 Moreover, the clade that is associated with more severe symptoms also had a higher ability to attach to epithelial cells and had higher virulence gene expression. 40 This suggests that bacteriophage repertoires are relatively stably associated with individual lineages within EHEC O55:O157.…”
Section: The Influence Of the Accessory Genome On Bacterial Pathogen mentioning
confidence: 99%
“…It is also important to point out that EHEC O55:O157 is not the only EHEC lineage within E. coli as at least 24 other E. coli lineages also acquired an enterohaemorrhagic lifestyle: the comparison of O55:O157 with three of these other lineages revealed that they independently acquired different bacteriophages that carry similar virulence gene repertoires. 42 In conclusion, specific bacteriophage repertoires appear to be vertically inherited within specific bacterial lineages contributing to lineage-specific fitness and virulence 39,40 while horizontal transfer of bacteriophages between phylogenetically quite distant groups allows for emergence of new pathogenic lineages with very similar phenotypes.…”
Section: The Influence Of the Accessory Genome On Bacterial Pathogen mentioning
confidence: 99%
“…Cases of EHEC infection normally present to health facilities as bloody diarrhoea although more severe complications can occur. The frequency of these complications is dependent on the toxin encoded; the presence of vtx2a has been shown to be associated with a more virulent infection [49] partly due to increased expression [50]. The ability to adhere to intestinal cells has also been shown to be associated with virulence and although EHEC, as with EPEC, normally adhere using the LEE [47], there are other mechanisms of attachment within E. coli and outbreaks have been caused by several different lineages of EHEC using non-LEE mediated attachment.…”
Section: Enterohemorrhagic E Coli (Ehec)mentioning
confidence: 99%
“…It was previously reported that E. coli O157:H7 isolates from lineage II produced less Stx2 than those from lineage I and I/II 28 ; however, our findings show that the Stx2 levels in strains from lineage II (PA40, 41) were not significantly different from strains belonging to lineage I (PA5, 31, 32, 49) or lineage I/II (PA22, 35,38,47). Second, although strains from clade 8 were suggested to produce higher Stx2 levels than isolates from other clades, 29,30 our data indicates this is not universal. In our study, clade 8 strain PA35 produced similar amounts of Stx2 as others clades, including clade 2 (PA31), clade 5 (22), clade 6 (PA38) and clade 7 (PA40, 41).…”
Section: Advances In Food Technology and Nutritional Sciences Issn 23mentioning
confidence: 63%
“…Several studies have concluded, for example, that lineage I and I/II isolates produce more Stx2 than lineage II isolates, 28 and that clade 8 isolates are high toxin producers compared to isolates from other clades. 29,30 Most studies measure Stx2 production by semi-quantitative commercial kits, 10 qPCR/microarray, 10,29,30 or by semi-quantitative western blots. 30 Concerning mRNA quantification, several studies have reported that Stx2 transcript levels do not always correlate with Stx2 toxin production.…”
mentioning
confidence: 99%